Impact of IoT and Revenue-Sharing on Single and Two-Stage Pricing Strategies for Food Supply Chains - Saeed, Hafsa (2020)
A Master of Science thesis in Engineering Systems Management by Hafsa Saeed entitled, “Impact of IoT and Revenue-Sharing on Single and Two-Stage Pricing Strategies for Food Supply Chains”, submitted in December 2020. Thesis advisor is Dr. Mohamed Ben-Daya. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).